2019
DOI: 10.1007/s11136-019-02317-3
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of the ICECAP-O in informal carers of people with dementia from eight European Countries

Abstract: Purpose The pressure on healthcare budgets remains high, partially due to the ageing population. Economic evaluation can be a helpful tool to inform resource allocation in publicly financed systems. Such evaluations frequently use health-related outcome measures. However, in areas such as care of older people, improving health outcomes is not necessarily the main focus of care interventions and broader outcome measures, including outcomes for those providing informal care, may be preferred when evaluating such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…The correlations between the CarerQol-7D utility score and the CarerQol-VAS, PT, ICECAP-O utility score and EQ-5D health problems score of the caregiver had the expected direction and were statistically significant, but for some a lower strength was found compared to what was expected. Previous research using these data found a strong and positive correlation between the CarerQol-7D and the ICECAP-O [34], a measure of overall capability well-being; in this study we report the same coefficient (0.53). As expected, the positive (negative) dimensions of the CarerQol-7D were positively (negatively) correlated with the CarerQol-VAS, although some only weakly.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The correlations between the CarerQol-7D utility score and the CarerQol-VAS, PT, ICECAP-O utility score and EQ-5D health problems score of the caregiver had the expected direction and were statistically significant, but for some a lower strength was found compared to what was expected. Previous research using these data found a strong and positive correlation between the CarerQol-7D and the ICECAP-O [34], a measure of overall capability well-being; in this study we report the same coefficient (0.53). As expected, the positive (negative) dimensions of the CarerQol-7D were positively (negatively) correlated with the CarerQol-VAS, although some only weakly.…”
Section: Discussionsupporting
confidence: 79%
“…A tariff for the UK is available to compute a composite score on a scale from 0 (‘no capability’) to 1 (‘full capability’) [ 33 ]. The ICECAP-O has been validated within the Actifcare project and appeared to be a valid measure of well-being in informal caregivers for people with dementia [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This raises some important considerations around the use of the ASCOT-Carer alongside other generic preference-based health-related quality-of-life measures. Although in a previous study, the ASCOT-Carer showed little overlap with the EQ-5D-3L, 17 some degree of overlap is expected with broader measures of quality of life, such as the ICEpop CAPability measure for Adults or Older Adults, [33][34][35] that requires further investigation. The inclusion of physical and mental health in the CarerQol also creates some challenges around the use of the CarerQol alongside generic measures of health because of the potential risk of double counting.…”
Section: Implications Of Findings and Future Researchmentioning
confidence: 91%
“…The medico-socioeconomic survey included three separate questionnaires: a medico-socioeconomic questionnaire developed by the project team, the EuroQol five Dimensions three Levels (EQ-5D-3 L) 22 questionnaire and the Icepop Capability Measure for Older People (ICECAP-O) questionnaire. 23 25 We tested the questionnaires in five older adults prior to the study.…”
Section: Methodsmentioning
confidence: 99%
“…The ICECAP-O assesses five dimensions of capability: attachment (love and friendship), security (thinking about the future without concern), role (doing things that make you feel valued), enjoyment (enjoyment and pleasure), and control (independence). 25 There are four response options for each dimension: no capacity, little capacity, high capacity and full capacity; therefore, there are 1024 potential “capacity states” for the entire instrument. ICECAP-O scores take a numerical value between 0 (no capacity) and 1 (full capacity).…”
Section: Methodsmentioning
confidence: 99%